SERIES DE FICCIÓN COMO MEDIO DE COEDUCACIÓN PARA ADOLESCENTES. ESTUDIO DE CASO: LAS DEL HOCKEY - Dr. Javier GIL-QUINTANA,Gr. Simón GIL-TÉVAR (Fonseca, Journal of Communication, 2023)
The TV series «Las del Hockey» (The Girls hockey / Les de l’hoquei) is a creation born from a final degree project in Audiovisual Communication at the Pompeu Fabra University (Barcelona), created by Ona Anglada, Laura Azemar, Natalia Boadas and Marta Vivet.The TV series has been produced by Brutal Media and has been also broadcast in TV3. Through a case study method, we analyze the TV series «Las del Hockey» with a mixed methodology.